2000
DOI: 10.1090/s0002-9947-00-02665-9
|View full text |Cite
|
Sign up to set email alerts
|

On the lack of null-controllability of the heat equation on the half-line

Abstract: Abstract. We consider the linear heat equation on the half-line with a Dirichlet boundary control. We analyze the null-controllability problem. More precisely, we study the class of initial data that may be driven to zero in finite time by means of an appropriate choice of the L 2 boundary control. We rewrite the system on the similarity variables that are a common tool when analyzing asymptotic problems. Next, the control problem is reduced to a moment problem which turns out to be critical since it concerns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 22 publications
6
69
0
Order By: Relevance
“…The theory has also been extended to semilinear problems (see, for example, [2,3,12,15,21,24,25]) and to equations in unbounded domains (see, for example, [13,33,34]; see also [31,41]). For the Stokes and Navier-Stokes equations we also refer the reader to [4,10,11,18,22,23,26,27,28].…”
mentioning
confidence: 99%
“…The theory has also been extended to semilinear problems (see, for example, [2,3,12,15,21,24,25]) and to equations in unbounded domains (see, for example, [13,33,34]; see also [31,41]). For the Stokes and Navier-Stokes equations we also refer the reader to [4,10,11,18,22,23,26,27,28].…”
mentioning
confidence: 99%
“…Regarding controllability aspects, Theorem 1.1 is strongly linked to the work [30], which proves that the solution of (1) cannot be controlled to zero when the initial datum y 0 belongs to the weighted Sobolev space L 2 (R * + , exp(x 2 /4)dx) (and y 0 ≡ 0). Such problem has also been studied from the observability point of view, which is a dual property of the controllability one.…”
Section: Commentsmentioning
confidence: 98%
“…Concerning Theorem 1.2. The controllability properties of (2) were analyzed in [30] for initial data y 0 ∈ L 2 (R * + ), and it was shown that there is no non-trivial initial condition in L 2 (R * + ) which can be driven to 0 with control functions u ∈ L 2 (0, T ) (in fact, [30] focuses of the equation…”
Section: Commentsmentioning
confidence: 99%
“…As regards the case where O is unbounded, which is the main objective of this work, this remained largely open. In some special cases, however, (O half-space), the boundary controllability was discussed in [14], [15].…”
Section: Introductionmentioning
confidence: 99%